Mengembangkan Inovasi dan Kreativitas dalam Membangun Bisnis Melalui Pelatihan Taktik Membangun Bisnis Bagi Mahasiswa - Nugroho, Mahendra Adhi; Setyorini, Dhyah; Novitasari, Budi Tiara; Nirbita, Betanika Nila (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
The low interest of students in building a business is a problem that must be considered together. Especially at this time, the role of higher education is more demanded to build enthusiasm, soul, and behavior in doing business. Training is one way to foster student interest in building a business. The purpose of this training is to provide students with an understanding of the importance of business to create independent students and an understanding of business building techniques. The method of implementing this training activity includes initial coordination activities, preparation, implementation of activities, and evaluation of activities. The training was held at the FEB UNY Auditorium with speakers Lutfi Hakim, SE, MBA, and MiM. The conclusion obtained from this activity is that students understand the techniques for building a business, and based on the survey results, it is found that the training has been carried out and is running well.